EU telecommunications law - Savin, Andrej, 1973- (Elgar European law, 2018)
EU Telecommunications Law provides a comprehensive overview of the current European regulatory framework as it applies to telecommunications and examines the challenges facing regulators in this sector. Key chapters focus on the selection of appropriate regulatory models that serve to encourage effective investment in next-generation networks and ensure their successful deployment. Andrej Savin provides an up to date overview of all the relevant sources, guiding the reader through these disparate materials in a simple and systematized way. In particular, the book provides analysis of the 2016 proposal for a European Electronic Communications Code (EECC). Using the 2009 Regulatory Framework on electronic communications as a basis the author analyses each of the 2009 framework's five main directives, comparing them with the changes proposed in the EECC.-